First-Principles Study on the Impact of Stress on Depassivation of Defects at a-SiO2/Si Interfaces - Liu, Xin; Liu, Yang; Zhu, Hao-Ran; Liu, Xue-Hua; Zhang, Wen-Li; Zuo, Xu (Frontiers in Materials, 2022)
The amorphous silicon dioxide-silicon (a-SiO2/Si) interface is an important part of silicon devices. It is difficult to avoid interface defects during the device production process. The passivated interface defects will undergo a depassivation reaction with the protons in the silicon dioxide generated by irradiation and convert to positively charged dangling bonds, thereby affecting device performance. In engineering practice, there is a final passivation layer on top of a-SiO2, and it is inevitable to introduce stress on the a-SiO2/Si interface. Therefore, studying the depassivation reaction mechanism of a-SiO2/Si interface defects under stress is of great significance to understand the performance degeneration in real devices. By using molecular dynamics and first-principles calculations, Pb defects at a-SiO2/Si(111) interface and Pb1 defects at a-SiO2/Si(100) interface are selected in this work to investigate the effect of stress on their depassivations. Biaxial strains are applied to the models, energy curves of the depassivation reactions under stress are calculated using the CI-NEB (Climbing Image Nudged Elastic Band) method, and transition states are identified. According to the Harmonic Transition State Theory(HTST), the reaction rate constants of the depassivation reactions of Pb and Pb1 defects at a certain temperature can be obtained. Finally, the relative concentration curves during depassivation reactions of PbH and Pb1H under stress and room temperature are obtained. Detailed data and figure analyses are presented to demonstrate differences between the two typical interface defects when depassivating under stress. Appropriate degrees of interface stress are proved to extend the depassivation time of defects, therefore prolonging the service life of devices.